Factors associated with the health seeking behavior of post menopausal syndrome among women, Lalitpur. - Maharjan,Grishma (2019)
ABSTRACT: Menopause is the unique stage of female reproductive life cycle..Menopause is perhaps the most striking event occurring during the middle age in women and represents the end of reproductive life. Although menopause is a universal phenomenon, there is a considerable variation among women regarding the age of attaining menopause and the manifestations of the menopausal signs and symptoms which are less prioritized issue in developing countries including Nepal. Thus,this study was carried out to determine the pattern, severity and health seeking behavior of women with menopausal symptoms in Newar community. A cross-sectional study was carried out in ward no 12 and 17 of Lalitpur municipality .Purposive sampling was used and the sample consisted of 264 postmenopausal women. Data was collected through face to face interviews using semi structured questionnaire and Menopause rating scale. Chi-square test was applies to test the significance of association between the severity and health seeking behavior at 95% confidence interval. The mean age of the postmenopausal women was found 51.75 years and Mean age of onset of menopause was found to be 47.5 years The duration of menopausal symptoms increases along with age which was found to be statistically significant for somatic symptoms (p=value 0.000) and Psychological value (p=0.011).Regarding the MRS Score 16.3% of them were having real problem with score more than 16 which is the cutoff point to seek the healthcare. Thus, the severity of the menopausal problem is associated with the health seeking behavior of the post menopausal women (p= 0.007 for psychological symptoms, p=0.045 for somatic symptoms). Also, revealed the reason for not seeking healthcare was lack of knowledge/awareness and ignorance. Only minority of the respondent were not seeking healthcare due to financial problem and misconception. Although, severity of post menopausal syndrome is associated with the health seeking behavior of women, large efforts are required to educate and make the women aware of menopausal problems. It must be focused in early recognition of problems and encouragement to seek healthcare so that discomforts related to menopausal problems can be reduced.